Salinity induced anatomical and morphological changes in Chloris gayana Kunth roots - Ceccoli, Gabriel; Ramos, Julio C.; Ortega, Leandro Ismael; Acosta, Juan M.; Perreta, Mariel Gladis (Universidad Nacional de Cuyo, 2020)
Chloris gayana Kunth is a grass species valuable as forage which was introduced into Argentina to be used as pasture in saline soils of subtropical and warm-temperate zones, given its good adaptability to drought, salinity and mild freezing. However, its tolerance varies according to the cultivar. In tetraploid cultivars, important reductions in yield have been observed. Here, a study of the variations produced on the root and stem system by salinity at different NaCl concentrations (0, 150 y 250 mM) was performed in the Boma cultivar, with the aim of determining the anatomical and morphological alterations produced by the salt excess. Plants cultivated with the highest level of salinity showed, in the whole, significant differences in the measured variables. A diminution in absolute values of the variables and a major reduction in vascular tissue dimensions were observed, which suggests that the lack of tolerance to salt stress could be related to a deficient adaptation to absorb and transport water and nutrients from the roots.